Probing Proteostatic Stress in Degenerating Photoreceptors Using Two Complementary In Vivo Reporters of Proteasomal Activity - Dexter, Paige M. (eNeuro, 2020)
Inherited retinal degenerations originate from mutations in >300 genes, many of which cause the production of misfolded mutant photoreceptor proteins that are ultimately degraded by the ubiquitin-proteasome system (UPS). It was previously shown that rod photoreceptors in multiple mouse models of retinal degeneration suffer from proteostatic stress consisting of an insufficient cellular capacity for degrading UPS substrates. In this study, we focused on a specific UPS component required for the degradation of a subset of proteasome targets: the substrate-processing complex formed by the AAA+ ATPase P97/VCP and associated cofactors. To assess whether P97 capacity may be insufficient in degenerating rods, we employed two complementary in vivo proteasomal activity reporters whose degradation is either P97-dependent or P97-independent. Retinal accumulation of each reporter was measured in two models of retinal degeneration: the transducin γ-subunit knock-out (Gγ(1)(-/-)) and P23H rhodopsin knock-in (P23H) mice. Strikingly, the patterns of reporter accumulation differed between these models, indicating that the proteostatic stress observed in Gγ(1)(-/-) and P23H rods likely originates from different pathobiological mechanisms, in which UPS substrate degradation may or may not be limited by P97-dependent substrate processing. Further, we assessed whether P97 overexpression could ameliorate pathology in Gγ(1)(-/-) mice, in which proteostatic stress appears to result from P97 insufficiency. However, despite P97 overexpression being aphenotypic in other tissues, the ∼2.4-fold increase in retinal P97 content was toxic to rods, which complicated the interpretation of the observed phenotype. Our results highlight the complexity of pathophysiological mechanisms related to degrading misfolded proteins in mutant photoreceptors.